2014
DOI: 10.1016/j.jacc.2013.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Coronary Artery Disease Secondary Prevention Prescriptions Among Outpatient Cardiology Practices

Abstract: Objectives This study assesses practice variation of secondary prevention medication prescription among coronary artery disease (CAD) patients treated in outpatient practices participating in the NCDR® PINNACLE Registry®. Background Among patients with CAD, secondary prevention with a combination of beta-blockers, angiotensin converting enzyme inhibitors/angiotensin receptor blockers, and statins reduces cardiac mortality and myocardial infarction (MI). Accordingly, every CAD patient should receive the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 20 publications
5
42
0
3
Order By: Relevance
“…Several studies have demonstrated substantial variation in the medical management of specific conditions across cardiology practices 12, 13, 14. To date, no study has measured the extent of variation in the delivery of common cardiac services across cardiology practices in the outpatient setting, specific services contributing to variation, or the association between intensity and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated substantial variation in the medical management of specific conditions across cardiology practices 12, 13, 14. To date, no study has measured the extent of variation in the delivery of common cardiac services across cardiology practices in the outpatient setting, specific services contributing to variation, or the association between intensity and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…An MOR of 1.0 would suggest no variation among physicians, and a greater MOR would suggest the presence of variation among individual physicians. An MOR >1.2 has been recognized as a marker of clinically significant variation 11, 12…”
Section: Methodsmentioning
confidence: 99%
“…Each of the original writing committees that developed the measures revised in this update identified secondary 12 Reports from the National Cardiovascular Data Registry PINNACLE Registry of ambulatory patients with CAD revealed that only 66 .5% (103 830 of 156 145) were receiving optimal medical therapy (OMT), including statins, 13 that 77 .8% (30 160 of 38 775) were prescribed statins, 14 and that uninsured patients were 6% less likely to receive lipid-lowering therapy . 15 Additionally, the study by Maddox and colleagues found substantial variation in prescription patterns by practice site .…”
Section: Gaps In Carementioning
confidence: 99%